Unliganded Thyroid Hormone Receptor α Regulates Developmental Timing via Gene Repression in Xenopus tropicalis - Choi, Jinyoung (Endocrinology, 2015)
Thyroid hormone (TH) receptor (TR) expression begins early in development in all vertebrates when circulating TH levels are absent or minimal, yet few developmental roles for unliganded TRs have been established. Unliganded TRs are expected to repress TH-response genes, increase tissue responsivity to TH, and regulate the timing of developmental events. Here we examined the role of unliganded TRα in gene repression and development in Xenopus tropicalis. We used transcription activator-like effector nuclease gene disruption technology to generate founder animals with mutations in the TRα gene and bred them to produce F1 offspring with a normal phenotype and a mutant phenotype, characterized by precocious hind limb development. Offspring with a normal phenotype had zero or one disrupted TRα alleles, and tadpoles with the mutant hind limb phenotype had two truncated TRα alleles with frame shift mutations between the two zinc fingers followed by 40–50 mutant amino acids and then an out-of-frame stop codon. We examined TH-response gene expression and early larval development with and without exogenous TH in F1 offspring. As hypothesized, mutant phenotype tadpoles had increased expression of TH-response genes in the absence of TH and impaired induction of these same genes after exogenous TH treatment, compared with normal phenotype animals. Also, mutant hind limb phenotype animals had reduced hind limb and gill responsivity to exogenous TH. Similar results in methimazole-treated tadpoles showed that increased TH-response gene expression and precocious development were not due to early production of TH. These results indicate that unliganded TRα delays developmental progression by repressing TH-response genes.